Qualitative Determination of Specific Protein Glycation Products by Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry Peptide Mapping - Humeny, Andreas; Kislinger, Thomas; Becker, Cord-Michael; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2002)
The nonenzymatic reaction between reducing sugars and proteins, known as the Maillard reaction, has received increased recognition from nutritional science and medical research. The development of new analytical techniques for the detection of protein-bound Maillard products is therefore crucial. In this study, we applied peptide mapping by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry to investigate the formation of structurally specific Maillard products on glycated lysozyme (AGE-lysozyme), produced upon incubation with D-glucose. In parallel, we synthesized Nε-(carboxymethyl)lysine-modified lysozyme (CML-lysozyme) and Nε-(carboxyethyl)lysine-modified lysozyme, two well-described glycation products, as model substances. 3-Deoxyglucosone-modified lysozyme and methylglyoxal-modified lysozyme were prepared as examples of glycation products incubated with dicarbonyl compounds. We were able to detect specific modifications on AGE-lysozyme, which were assigned to CML, imidazolone A, and the Amadori product.
UnivIS-Import:2015-03-09:Pub.2002.nat.dchph.llmch.qualit
Keywords: Imidazolone A; Maillard reaction; MALDI-TOF-MS peptide mapping; N; Protein glycation